Possible Protective Effect of Diacerein on Doxorubicin-Induced Nephrotoxicity in Rats - Marwa M. M. Refaie; Entesar F. Amin; Nashwa F. El-Tahawy; Aly M. Abdelrahman (Journal of Toxicology)
Nephrotoxicity is one of the limiting factors for using doxorubicin (DOX). Interleukin 1 has major role in DOX-induced nephrotoxicity, so we investigated the effect of interleukin 1 receptor antagonist diacerein (DIA) on DOX-induced nephrotoxicity. DIA (25 and 50 mg/kg/day) was administered orally to rats for 15 days, in the presence or absence of nephrotoxicity induced by a single intraperitoneal injection of DOX (15 mg/kg) at the 11th day. We measured levels of serum urea, creatinine, renal reduced glutathione (GSH), malondialdehyde (MDA), total nitrites (NOx), catalase, and superoxide dismutase (SOD). In addition, caspase-3, tumor necrosis factor alpha (TNFα), nuclear factor kappa B (NFκB) expressions, and renal histopathology were assessed. Our results showed that DOX-induced nephrotoxicity was ameliorated or reduced by both doses of DIA, but diacerein high dose (DHD) showed more improvement than diacerein low dose (DLD). This protective effect was manifested by significant improvement in all measured parameters compared to DOX treated group by using DHD. DLD showed significant improvement of creatinine, MDA, NOx, GSH, histopathology, and immunohistochemical parameters compared to DOX treated group.